The Comparison Between Computational Design Method with Particle Swarm Optimization Algorithm for Mini Hydro Power Plant - Mohd Nasir, Abdul Muiz; Mohamad Nor, Ahmad Fateh (Evolution in Electrical and Electronic Engineering, 2022)
This project's study focuses on the creation of a Particle Swarm Optimization (PSO) platform for designing a mini hydro-power plant. The usage of non-fossil fuel and green energy has increased dramatically, with renewable energy's proportion of worldwide overall energy increasing from 2% to 7% in 10 years, owing to its dependability and sharp cost reduction. The mini hydro-power plant is a renewable energy plant that offers several benefits over wind and solar renewable energy plants of the same size. Hydropower is completely pure, therefore it will never run out until the water supply is cut off, the power generation emits no pollution into the atmosphere, and it is the most dependable renewable energy source known. This paper discusses the proper selection of mini hydro-power plant components such as turbine type, penstock size, and net head length, which are the major components of the power station. The basis of the findings of the design of a mini hydro-power plant for Tebing Tinggi River in Perak, with a flow rate of 0.1650 m3/sec. The length, diameter, minimum wall thickness, and net head of the penstock are 467m, 334mm, 2.085mm, and 125m, respectively. The penstock pipe was made of welded steel, and the appropriate turbine was the Turgo, which is an impulse type. The PSO method created was able to discover the specifications of all the components that would be used to build a mini hydro-power plant. For this objective, the PSO algorithm was developed using the MATLAB program and the coding algorithm environment. The PSO algorithm was able to produce the same results as the design specifications that were calculated.